The general theory of employment, interest and money - Keynes, John Maynard (London : Macmillan, 1998)
This book emphasizesd on all the Gordian knots of pre-Keynesian discussion of the trade cycle and propounded a new approach to the determination of the level of economic activity, the problems of employment and unemployment, the causes of inflation, the strategies of budgetary policy.
Includes index
aia 11/2/14; osa 20/6/14
Loans
Keywords: Economics; Money; Monetary policy; Interest